Proposal for a unified nomenclature for target-site mutations associated with resistance to fungicides - Mair, W.; Lopez-Ruiz, F.; Stammler, G.; Clark, W.; Burnett, F.; Hollomon, D.; Ishii, H.; Thind, T.; Brown, J.; Fraaije, B.; Cools, H.; Shaw, M.; et al. (John Wiley & Sons Ltd., 2016)
Evolved resistance to fungicides is a major problem limiting our ability to control agricultural, medical and veterinary pathogens and is frequently associated with substitutions in the amino acid sequence of the target protein. The convention for describing amino acid substitutions is to cite the wild-type amino acid, the codon number and the new amino acid, using the one-letter amino acid code. It has frequently been observed that orthologous amino acid mutations have been selected in different species by fungicides from the same mode of action class, but the amino acids have different numbers. These differences in numbering arise from the different lengths of the proteins in each species. The purpose of the present paper is to propose a system for unifying the labelling of amino acids in fungicide target proteins. To do this we have produced alignments between fungicide target proteins of relevant species fitted to a well-studied ‘archetype’ species. Orthologous amino acids in all species are then assigned numerical ‘labels’ based on the position of the amino acid in the archetype protein.